Ecologia da comunidade aquática de um riacho de 1ª ordem da Mata Atlântica: relações entre variáveis estruturais e bióticas em uma reserva de biosfera tropical - Vilella, Fábio Silveira (2002)
This study was developed in arroio Carvão, a 1ª order stream at the Maquiné watershed, in the southern part of Atlantic Rain Forest, Brazil. The headwaters are within the Serra Geral Biological Reserve, a conservation unit that is a regional biodiversity core area of the Atlantic Forest Biosphere Reserve. The research was developed to identify the role of physical and chemical variables of the environment and the interactions of phoresis between species as elements that influence community structure in the stream. The results indicate the existence of a hierarchical relationship between the environmental variables and its influence on the community structure. It also reveals that morphological features and adaptations of the fauna to the lotic environmental pressure could turn highly elaborate and efficient, allowing the animals to neutralize or even transpose the environmental pressure. Phoresis, a non-negative form of interaction between species, represents an alternative way for animals morphologically less adapted to the lotic system, to colonize and establish on more favorable places in the stream. It is also discussed the evolutionary significance of phoresis.